A Meta-Analysis of the Equity Premium - Casper van Ewijk; Henri L.F. de Groot; Coos Santing (Tinbergen Institute, 2010)
The equity premium is a key parameter in asset allocation policies. There is a vigorous debate in the literature regarding the actual measurement of the equity premium, its size and the determinants of its variation. This study aims to take stock of this literature by means of a meta-analysis. We identify how the size of the equity premium depends on the way it is measured, along with its evolution over time and its variation across regions in the world. We find that the equity premium is significantly lower if measured by ex ante methods rather than ex post, in more recent periods, and for more developed countries. In addition, looking at the underlying fundamentals, we find that larger volatility in GDP growth tends to raise the equity premium while a higher nominal interest rate has a negative impact on the equity premium.
Keywords: D53; E44; G12; N20; 330; equity premium; meta-analysis; Kapitaleinkommen; Risikoprämie; Meta-Analyse